THE INFLUENCE OF AFFECTIVE COMMITMENT, CONTINUANCE COMMITMENT, AND NORMATIVE COMMITMENT ANALYSIS TO PERFORMANCE WITH MODERATION ORGANIZATIONAL CULTURE (Case Study on Institute Agama Islam Negeri (IAIN) Walisongo Semarang) - Sutaat, 12.52.02.0073; Suko Priyono, Bambang (Jurnal Mahasiswa Pasca Sarjana, 2014)
This research that is done in Institute Agama Islam Walisongo Semarang. Data used by primary data taken with questionnaire with 82 respondents for sample research. The writer did the reseach by using purposive sampling, with some criteria. Those criteria are the respondents have to had level stratum -2 for level education and tree year minimum in a work periode. Analysis appliance weared by instrument test, the test reliability, and while the test models, test the Adj R2 (coefficient of determination), Test the hypothesizing used regression analysis, test the F Test (Goodness of Fit), and test the moderation using analysis path (path analysis). The results of the analysis in this study resulted in regersi determination coefficient of 0.423, or in other words, changes in performance can be influenced by effective commitment, continuance commitment, normative commitment and organizational culture of 43.3%. The results of this study indicate that affective commitment does not affect the employee performance, ccontinuance commitment has the influence a significant effect on employee performance, normative commitment does not effect on employee performance, organizational culture did not moderate the influence of affective organizational commitment to employee performance, organizational culture didât Â moderate the influence of continuance organizational commitment to employee performance and organizational culture moderates the effect of normative commitment on employee performance Keywords: Affective Commitment, Continuance Commitment and Normative Commitment, Organizational Culture and Employee Performance.